Renewable energy on animal farms: support system and practical application - Csatári, Nándor (Acta Agraria Debreceniensis, 2014)
Renewable energy applications were examined in animal farms. The investment support system for animal farms – which has renewable elements – has been summarized through analyzing the legislation and future prospects. The most important in this topic is the Animal Farm Modernization Support, which had several application periods during the 2007–2013 CAP budgets. For analyzing practical application of renewable energies interviews and farm visits have done in Hajdú-Bihar County. The questions covered the general attributes of the farms and the details of the (existing or planned) renewable energy application. In terms of economic analysis saving, the investment return time and the employment effect were examined. The results show wide variety of applied renewable energy application. The investment supports plays great role in renewable energy projects by lowering the return time; and through additional points in application assessing, which is an incentive for farmers to include renewable energy element in their modernization projects.